Gugatan Tidak Dapat Diterima (Niet Ontvankelijke Verklaard) dalam Gugatan Cerai Gugat di Pengadilan Agama Badung - I Gusti Agung Ketut Bagus Wira Adi Putra; Ida Ayu Putu Widiati; Ni Made Puspasutari uj (Jurnal Konstruksi Hukum, 2020)
In the course of the household, there are always disputes between husband and wife that cannot be resolved and lead to divorce. This study aims to determine the legal consequences of an unacceptable lawsuit in a lawsuit divorce case in decision number 0063 / Pdt.G / 2017 / PA.Bdg and to find out that the judge's consideration in deciding a lawsuit cannot be accepted in a divorce suit in decision number 0063 / Pdt.G / 2017 / PA.Bdg. This study uses a normative legal research method with a case approach. The results of the study show that in Law Number 1 of 1974 concerning marriage in Article 39 paragraph (2) of the Marriage Law and its explanation it states that divorce can be carried out if it is in accordance with predetermined reasons. An unacceptable decision (NO) is a decision stating that a lawsuit cannot be accepted, because of formal defects. Then, the reasons that cause the lawsuit to be unacceptable due to formal defects are invalid power of attorney, lawsuit filed by parties who have no legal interest, in person error suit, lawsuit beyond competence, lawsuit against libel, premature lawsuit and lawsuit expired. Libel's lawsuit is vague or unclear and the cause of obscuur libel's lawsuit in this case is an incomplete petitum, therefore the lawsuit cannot be accepted